2010
DOI: 10.1530/eje-10-0330
|View full text |Cite
|
Sign up to set email alerts
|

Proinsulin levels in patients with pancreatic diabetes are associated with functional changes in insulin secretion rather than pancreatic β-cell area

Abstract: Introduction: Hyperproinsulinaemia has been reported in patients with type 2 diabetes. It is unclear whether this is due to an intrinsic defect in b-cell function or secondary to the increased demand on the b-cells. We investigated whether hyperproinsulinaemia is also present in patients with secondary diabetes, and whether proinsulin levels are associated with impaired b-cell area or function. Patients and methods: Thirty-three patients with and without diabetes secondary to pancreatic diseases were studied p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Proinsulin and C-peptide are two proteins that have received particular attention as elevated levels of both peptides are correlated with onset and progression of diabetes. 100 While proinsulin constitutes a minor fraction of the secreted insulin, its release is significantly increased in type II diabetics and in patients with impaired glucose tolerance (a pre-diabetic state with a slightly elevated blood glucose level). 100 It is not yet clear whether the increased level of proinsulin in diabetics is due to a defect in the insulin processing machinery or merely the result of increased secretory demand on β cells that results in depletion of mature insulin and thus, the need to secrete immature granules.…”
Section: Type II Diabetes and Islet Amyloid Polypeptide (Iapp)mentioning
confidence: 99%
See 1 more Smart Citation
“…Proinsulin and C-peptide are two proteins that have received particular attention as elevated levels of both peptides are correlated with onset and progression of diabetes. 100 While proinsulin constitutes a minor fraction of the secreted insulin, its release is significantly increased in type II diabetics and in patients with impaired glucose tolerance (a pre-diabetic state with a slightly elevated blood glucose level). 100 It is not yet clear whether the increased level of proinsulin in diabetics is due to a defect in the insulin processing machinery or merely the result of increased secretory demand on β cells that results in depletion of mature insulin and thus, the need to secrete immature granules.…”
Section: Type II Diabetes and Islet Amyloid Polypeptide (Iapp)mentioning
confidence: 99%
“…100 It is not yet clear whether the increased level of proinsulin in diabetics is due to a defect in the insulin processing machinery or merely the result of increased secretory demand on β cells that results in depletion of mature insulin and thus, the need to secrete immature granules. 100 Preliminary studies on the interaction between hIAPP and proinsulin have revealed weaker binding affinity of proinsulin to hIAPP and reduced inhibition of hIAPP aggregation in the presence of proinsulin as compared to mature insulin. 88,96 This indicates that either proinsulin has a different structure at the interaction interface with hIAPP or there are differences in the flexibility of the proinsulin sequence.…”
Section: Type II Diabetes and Islet Amyloid Polypeptide (Iapp)mentioning
confidence: 99%
“…In human diabetics, increased proinsulin concentrations may be found in plasma, which is considered to be an indicator of β-cell dysfunction (Breuer et al, 2010;Wang and Osei, 2011). Knowledge in cats is limited to obese individuals, which revealed abnormal proinsulin to insulin ratios during IVGTTs (Kley et al, 2008).…”
Section: Insulin Metabolic Effects and Pathophysiology* Insulin Synmentioning
confidence: 99%
“…The correlations remained significant when stratifying participants into two groups according to the median BMI and serum insulin levels. In the present study, we examined this relationship using PI, which has served as a marker of pancreatic β‐cell dysfunction. In a recent study, we showed that, among several estimation methods of β‐cell function, fasting PI was the most sensitive to glucose intolerance.…”
Section: Discussionmentioning
confidence: 95%